Investigating curling athletes' effective communication skills - Alaeddinoğlu, Vahdet (2022)
This study aims to reveal the relationship levels of the forms of communication of curling athletes. 141 (Xage=21.32 ± 2.08; Xsporting age=8.91 ± 2.87) athletes, 55 women, and 86 men continued active sports in the 2021 Turkish Curling leagues, voluntarily took part in the research. In our research, the "Communication Skills Scale", "Scale of Effective Communication in Team Sports" (SECTS) and a survey, including Demographic information, were applied. The obtained data were analyzed through SPSS 22.00 Statistics Software Package. According to the research results, the correlation values between the scores of the "Communication Skills Scale" (CSS) and the "Acceptance & Positive Conflict Dimension" and the "Scale of Effective Communication in Team Sports" (SECTS) were significantly and positively related. Besides, the genders of the athletes were positively significant within the communication skills scale sub-dimension and the dimensions of discernment and conflict.